Bionomics and control of the fruit flies, Ceratitis capitata (Wied.) and Pterandrus rosa (Ksh.), in the Western Cape Province - Myburgh, Andre Cyril (Stellenbosch : Stellenbosch University, 2012)
Thesis (DScAgric)--Stellenbosch University, 1956.